Business and Management Education in Transitioning and Developing Countries : a Handbook. - McIntyre, John R. (Taylor and Francis, 2014)
Business education is a critical ingredient in establishing a viable middle class of managers in transitioning and developing economies. Compiled in association with the Center for International Business Education and Research, this comprehensive examination of business and management education, pedagogical models, and curricula innovations in institutions around the world is the first such work to emphasize emerging markets.